Classroom assessment techniques - Angelo, Thomas A (Jossey-Bass Publishers, 1993)
This revised and greatly expanded edition of the 1988 handbook offers teachers at all levels how-to advise on classroom assessment, including: What classroom assessment entails and how it works. How to plan, implement, and analyze assessment projects. Twelve case studies that detail the real-life classroom experiences of teachers carrying out successful classroom assessment projects. Fifty classroom assessment techniques Step-by-step procedures for administering the techniques Practical advice on how to analyze your data.; Rev. ed. of: Classroom assessment techniques: a handbook for faculty, 1988; Includes bibliographical references (p. 407-414) and index